Selective esterification of glycerol with acetic acid or lauric acid over rod-like carbon-based sulfonic acid functionalized ionic liquids. (1st November 2017) - Sun, Yingnan; Hu, Jianglei; An, Sai; Zhang, Qingqing; Guo, Yihang; Song, Daiyu; Shang, Qingkun
Graphical abstract: Highlights: Rod-like carbon-based sulfonic acid functionalized acidic ionic liquids are prepared. The materials exhibit high catalytic activity in glycerol esterification reaction. High density of super strong Brønsted acid sites plays key role to the activity. Surface hydrophilicity and rod-like nanostructure positively influence the activity. The materials can be reused 3 times without obvious activity loss. Abstract: A series of rod-like nitrogen-containing carbon-based sulfonic acid functionalized ionic liquids, [ Pr SO3 HN][SO3 CF3 ]/C, with tunable Brønsted acid site densities are fabricated by quaternary ammonization of hydrothermally prepared nitrogen-containing carbon nanorods with 1, 3-propanesultone followed by anion exchange with trifluoromethanesulonic acid. The materials are successfully applied in the selective esterification of glycerol with acetic acid or lauric acid to the value-added glycerol esters including triacetain, glycerol monolaurate and glycerol dilaurate. The excellent esterification activity of the [ Pr SO3 HN][SO3 CF3 ]/C nanorods strongly depends on their Brønsted acid nature; additionally, the morphological characteristics, surface hydrophilicity and flexible polycyclic aromatic carbon structure influence the catalytic activity to some extent. The [ Pr SO3 HN][SO3 CF3 ]/C-2 nanorod with high density of super strong Brønsted acid sites and perfect rod-like nanostructure exhibits the highest esterification activity, and its activity outperforms Amberlyst-15, propylsulfonic acid functionalized SBA-15, the [ Pr SO3 HN][SO3 CF3 ] group functionalized carbonaceous framework obtained by high temperature (600 °C) calcination as well as homogeneous p -toluenesulfonic acid. Moreover, the catalyst can be reused three times without significant activity loss, attributing to the chemical interactions between the [ Pr SO3 HN][SO3 CF3 ] groups and the carbon framework.